Behavior of bounded solutions for some almost periodic neutral partial functional differential equations. (26th August 2016) - Ait Dads, El Hadi; Es‐sebbar, Brahim; Ezzinbi, Khalil; Ziat, Mohamed
Abstract : We establish a Bochner type characterization for Stepanov almost periodic functions, and we prove a new result about the integration of almost periodic functions. This result is then used together with a reduction principle to investigate the nature of bounded solutions of some almost periodic partial neutral functional differential equations. More specifically, we prove that all bounded solutions on R are almost periodic. Copyright © 2016 John Wiley & Sons, Ltd.